2019
DOI: 10.1162/jocn_a_01360
|View full text |Cite
|
Sign up to set email alerts
|

Brain and Cognitive Mechanisms of Top–Down Attentional Control in a Multisensory World: Benefits of Electrical Neuroimaging

Abstract: In real-world environments, information is typically multisensory, and objects are a primary unit of information processing. Object recognition and action necessitate attentional selection of task-relevant from among task-irrelevant objects. However, the brain and cognitive mechanisms governing these processes remain not well understood. Here, we demonstrate that attentional selection of visual objects is controlled by integrated top–down audiovisual object representations (“attentional templates”) while revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 99 publications
(123 reference statements)
0
30
0
Order By: Relevance
“…We have recently shown that combining the added benefits of EN measures and wellunderstood EEG correlates of cognitive processes allows for distinguishing between different cognitive accounts of multisensory attentional control (Matusz et al 2019b).…”
Section: The Present Studymentioning
confidence: 99%
See 2 more Smart Citations
“…We have recently shown that combining the added benefits of EN measures and wellunderstood EEG correlates of cognitive processes allows for distinguishing between different cognitive accounts of multisensory attentional control (Matusz et al 2019b).…”
Section: The Present Studymentioning
confidence: 99%
“…In an EN framework, such differences would be readily detected as GFP differences between experimental conditions over the N2pc time-window (for more info on how GFP can grasp differences in the brain mechanisms behind the N2pc, see Matusz et al 2019b).…”
Section: Data Analysis Designmentioning
confidence: 99%
See 1 more Smart Citation
“…For Cifar-10 and Cifar-100 experiments, ResNet-32, SENet-32, and WideResNet (28,10) are used as the basic structures, and the proposed "CE-unit" modules are embedded after specific convolutional layers. For comparison, SENet-32 only adds two SE-unit modules on the basis of ResNet-32 structure, and does not take the grouping convolution operation.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…The attention mechanism of simulated visual attention design can focus the computing power of the model on key tasks to avoid interference from the background environment. Attention models are usually divided into three types: bottom-up attention models [9], [10], top-down attention models [11], [12], top-down and bottom-up attention models [13], [14]. By simulating visual attention, the ITTI model [15] introduces attention mechanism for the first time and uses it for saliency detection tasks.…”
Section: Introductionmentioning
confidence: 99%